A Cross-Sectional Study on Evaluation of Ige Levels in Subjects with Atopic Dermatitis (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by itching and eczematous lesions. The prevalence of atopic dermatitis in children is about 15%. The pathogenesis of AD multifactorial and is involved with genetic susceptibility, skin barrier defects, environmental factors and immunologic dysregulation.Aim and Objective of the study: The aim and objectives of the study were to estimate immunoglobulin E levels in subjects with atopic dermatitis and to correlate IgE levels with severity of AD symptoms.Materials and Methods: Data were collected based on a questionnaire applied during the routine visit. Parents of illiterate children were asked to help them filling in the questionnaire, which comprised questions regarding symptoms and activities of daily life of patients. The questions were adjusted from the questionnaire validated by Yosipovitch et al., in 2002, describing pruritus in atopic dermatitis patients. The physical examination to assess severity of disease was performed by a dermatologist, according to the criteria established by Rajka and Langeland who divided AD into mild, moderate and severe disease.Results: We included a total of 60 children presented with atopic dermatitis, based on the inclusion and exclusion criteria. Out of which 60 total study subjects 32 were males and 28 were females. The mean age in years was 9.6±5.47 years. We categorised 60 children based on association with other manifestations which include subjects with only atopic dermatitis 22 (36.6%), atopic dermatitis with asthma 28 (46.6%), atopic dermatitis with allergic rhinitis 27 (45%), and atopic dermatitis with asthma and allergic rhinitis 22 (36.6%). We further categorised the study subjects based on the severity of clinical symptoms of atopic dermatitis, we observed that 28% had mild symptoms, 54% had moderate symptoms and 18% had severe symptoms.Discussion and conclusion: : In conclusion, hyper-IgE in patients with eczema is independently associated with asthma, more severe atopy and more severe eczema during early childhood and adolescence. IgE > 2000 IU/L may be a tool to aid prognostication of this chronic relapsing dermatological disease and its progression to other atopic disorders.